The Application Of Oxytocin Massage To Increase Breast Milk Production In Postpartum Mothers With Sectio Caesarea: Case Report - Nova Dwi Pramesti; Emi Lindayani (Universitas Pahlawan Tuanku Tambusai, 2025)
Optimal breast milk production is essential for the health of the baby. However, postpartum sectio caesarea (SC) mothers often experience obstacles in breastfeeding due to the disruption of oxytocin hormone stimulation. Oxytocin massage is one of the nonpharmacological methods that can stimulate milk production. This study aims to determine the application of oxytocin massage to increase breast milk production in postpartum SC mothers at RSUD Umar Wirahadikusumah. The research method used a descriptive case report study design through a nursing care process approach by integrating EBN on one post-SC mother subject who experienced breastfeeding disorders. Implementation of oxytocin massage was carried out for four days with a frequency of twice a day for 15-20 minutes. The evaluation used an observation sheet containing 13 indicators of breast milk production. The results showed an increase in breast milk production characterized by breast milk that began to gush when the areola was squeezed, the baby suckled well, the baby's micturition frequency increased to 8 times per day, and the baby looked satisfied after feeding. This study concludes that oxytocin massage effectively increases breast milk production in SC postpartum mothers by stimulating the oxytocin hormone. This intervention can be part of nursing care to overcome ineffective breastfeeding non-pharmacologically. Keywords: Breast milk production, oxytocin massage, postpartum mother, sectio caesarea